Elasmopus thalyae sp. nov. (Crustacea: Amphipoda: Maeridae), a new benthic species from soft and hard bottoms of Arcachon Bay (SE Bay of Biscay) - Gouillieux, Benoit; Sorbe, Jean Claude (Zootaxa, 2015)
A new species of Elasmopus is described and figured from specimens collected in different benthic communities of Arcachon Bay. It can be distinguished from its closest relative E. rapax by the palmar ornamentation of male gnathopod 2 propodus (shelf and 2 teeth). It preferentially lives on hard bottoms (in mussel fouling of navigation buoys, Sabellaria spinulosa reefs, algal rocky bottoms, Laminaria and Saccorhiza bulbs and as epibiont on the carapace of Maja brachydactyla) but also less abundantly on naked sandy bottoms. An identification key of Atlantic and Mediterranean European species is also given.